The structural and optical constants of Ag2S semiconductor nanostructure in the Far-Infrared - Zamiri, Reza (2015)
Background: In this paper a template-free precipitation method was used as an easy and low cost way to synthesize Ag2S semiconductor nanoparticles. The Kramers-Kronig method (K-K) and classical dispersion theory was applied to calculate the optical constants of the prepared samples, such as the reflective index n(omega) and dielectric constant epsilon(omega) in Far-infrared regime. Results: Nanocrystalline Ag2S was synthesized by a wet chemical precipitation method. Ag2S nanoparticle was characterized by X-ray diffraction, Scanning Electron Microscopy, UV-visible, and FT-IR spectrometry. The refinement of the monoclinic beta-Ag2S phase yielded a structure solution similar to the structure reported by Sadanaga and Sueno. The band gap of Ag2S nanoparticles is around 0.96 eV, which is in good agreement with previous reports for the band gap energy of Ag2S nanoparticles (0.9-1.1 eV). Conclusion: The crystallite size of the synthesized particles was obtained by Hall-Williamson plot for the synthesized Ag2S nanoparticles and it was found to be 217 nm. The Far-infrared optical constants of the prepared Ag2S semiconductor nanoparticles were evaluated by means of FTIR transmittance spectra data and K-K method.